Effect of water temperature and quality on the setting time of alginate impression materials - Suliman, Muhammad Syahmie; Mohamed Hanaphi, Nur Hakim; Nasir, Siti Hajjar; Cheong, Joo Ming; Mustaffa, Musliana (Kulliyyah of Dentistry, International Islamic University Malaysia, 2021)
Introduction: Alginates are materials used to make an impression and it is a popular choice due to its ability to reproduce detailed anatomical impressions of teeth. Water temperature during the mixing of alginates is highly sensitive and small differences in temperature may change the rate of the setting process of alginates. This study was conducted to investigate the effect of different water temperature and different water quality on the setting time of alginate. Material and methods: 3 sets of normal setting alginate were mixed in 3 different water temperatures (32º C, 23º C, 2º C). After 10 seconds of mixing, 1ml of alginate was loaded onto a rheometer to record the time taken for alginate to set. The test was repeated by using either distilled water or tap water at a constantwater temperature at 23º C. The significance of the differences between different temperature groups and water types against alginate setting time were also investigated. Results: In terms of water temperature, mixing of alginate with 32º C water has the shortest mean setting time of 71.34s, followed by 23º C water at 85.18s and 2º C water has the longest mean setting time of 99.36s. Distilled water allows longer setting time of 90.86s compared to tap water at 86.52s. One-way ANOVA analysis showed significant difference between the different water temperature on the setting time of alginate (p<0.05). However, there was no significant difference between different water quality on the setting time of alginate (p>0.05). Conclusion: Lower water temperature resulted in longer alginate setting time. Distilled water allows for longer setting time of alginate compared to tap water.